2014
DOI: 10.1111/ele.12371
|View full text |Cite
|
Sign up to set email alerts
|

Habitat structure and the evolution of diffusible siderophores in bacteria

Abstract: Bacteria typically rely on secreted metabolites, potentially shareable at the community level, to scavenge resources from the environment. The evolution of diffusible, shareable metabolites is, however, difficult to explain because molecules can get lost, or be exploited by cheating mutants. A key question is whether natural selection can act on molecule structure to control loss and shareability. We tested this possibility by collating information on diffusivity properties of 189 secreted iron-scavenging side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
97
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 48 publications
(103 reference statements)
2
97
0
Order By: Relevance
“…13). In many cases, a likely important factor enabling coexistence is spatial structure (62)(63)(64), whereby spatial segregation of nonproducers and producers limits the exploitative potential of the former. In one of the few studies investigating interactions between antibiotics and social behaviors in bacteria, Diard et al (14) assessed the in vivo impact of ciprofloxacin on competition between virulent cooperative Salmonella enterica serovar Typhimurium and avirulent defectors.…”
Section: Discussionmentioning
confidence: 99%
“…13). In many cases, a likely important factor enabling coexistence is spatial structure (62)(63)(64), whereby spatial segregation of nonproducers and producers limits the exploitative potential of the former. In one of the few studies investigating interactions between antibiotics and social behaviors in bacteria, Diard et al (14) assessed the in vivo impact of ciprofloxacin on competition between virulent cooperative Salmonella enterica serovar Typhimurium and avirulent defectors.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has long been suspected that many siderophores might remain cell associated after secretion (25,(55)(56)(57), evidence for this notion is limited and restricted to a few bacterial species. Furthermore, aside from the few studies on amphiphilic siderophores and pyoverdine, the mechanisms for privatization appear to be largely unexplored (23,24,26).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that adherence of FeEnt to the surface of E. coli is almost entirely mediated by FepA (58), but the mechanism for apo-Ent adherence is unclear, as studies typically measure adsorbance and transport of radiolabeled iron-siderophore complexes into cells, not aposiderophores (59). Due to the hydrophobicity of apo-Ent, it is possible that it remains associated with the cell surface after secretion (25,56). We have not addressed the mechanism of Ent privatization, but we have found that iron chelated with transferrin supports growth of E. coli only when cells are at sufficient population densities or if exogenous enterochelin is added.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many bacteria engage in mutualistic behaviors such as siderophore production, which assists the whole bacterial population in iron-scavenging behaviors [28] (although note that this behavior may decline with the spatial scale of competition [29]). Assistance provided by a coinfection may also be a byproduct of other processes.…”
Section: Resource Modulationmentioning
confidence: 99%